Effects of Spring Migration Distance on Tree Swallow Reproductive Success Within and Among Flyways - Gow, Elizabeth A.; Knight, Samantha M.; Bradley, David W.; Clark, Robert G.; Winkler, David W.; Bélisle, Marc; Berzins, Lisha L.; Blake, Tricia; Bridge, Eli S.; Burke, Lauren; Dawson, Russell D.; Dunn, Peter O.; et al. (Frontiers in Ecology and Evolution, 2019)
During migration, animals may experience high rates of mortality, but costs of migration could also be manifested through non-lethal carry-over effects that influence individual success in subsequent periods of the annual cycle. Using tracking data collected from light-level geolocators, we estimated total spring migration distance (from the last wintering sites to breeding sites) of tree swallows (Tachycineta bicolor) within three major North American flyways. Using path analysis, we then assessed direct and indirect effects of spring migration distance on reproductive performance of individuals of both sexes. When these data were standardized by flyway, females fledged 1.3 fewer young for every 1017 km they travelled, whereas there was no effect of migration distance on reproductive success in males. In comparison, when these data were standardized across all individuals and not by flyway, longer migrations were associated with 0.74 more young fledged for every 1017 km travelled by females and 0.26 more young fledged for every 1186 km migrated by males. Our results suggest that migration distance carries over to negatively influence female reproductive success within flyways but the overall positive effect of migration distance across flyways likely reflects broader life-history differences that occur among breeding populations across the tree swallow range.